Berberine-loaded targeted nanoparticles as specific Helicobacter pylori eradication therapy: in vitro and in vivo study. (January 2015) - Lin, Yu-Hsin; Lin, Jui-Hsiang; Chou, Shen-Chieh; Chang, Shu-Jen; Chung, Chun-Chia; Chen, Yueh-Sheng; Chang, Chiung-Hung
Aim: The aim of this work was to develop fucose-conjugated nanoparticles and control the release of berberine, and demonstrate that these particles come into contact with Helicobacter pylori and enhance the suppressive effect of berberine on H. pylori growth.Materials & methods: Fucose–chitosan/heparin nanoparticle-encapsulated berberine was prepared and delivery efficiency was monitored by confocal laser scanning microscopy. Anti- H. pylori activities were investigated by determining the calculated bacterial colonies and immunohistochemistry staining analysis.Results: Analysis of a simulated gastrointestinal medium indicated that the proposed drug carrier effectively controls the release of berberine, which interacts specifically at the site of H. pylori infection, and significantly increases berberine's suppressive effect on H. pylori growth. In an in vivo study, the berberine-loaded fucose-conjugated nanoparticles exhibited an H. pylori clearance effect.Conclusion: These findings indicate that berberine-loaded fucose-conjugated nanoparticles exert an H. pylori clearance effect and effectively reduce gastric inflammation in an H. pylori -infected animal study. Original submitted 19 November 2013; Revised submitted 4 March 2014